Supramolecular Aptamers on Graphene Oxide for Efficient Inhibition of Thrombin Activity - Ting-Xuan Lin (Frontiers in Chemistry, 2019)
Graphene oxide (GO), a two-dimensional material with a high aspect ratio and polar functional groups, can physically adsorb single-strand DNA through different types of interactions, such as hydrogen bonding and π-π stacking, making it an attractive nanocarrier for nucleic acids. In this work, we demonstrate a strategy to target exosites I and II of thrombin simultaneously by using programmed hybrid-aptamers for enhanced anticoagulation efficiency and stability. The targeting ligand is denoted as Supra-TBA15/29 (supramolecular TBA15/29), containing TBA15 (a 15-base nucleotide, targeting exosite I of thrombin) and TBA29 (a 29-base nucleotide, targeting exosite II of thrombin), and it is designed to allow consecutive hybridization of TBA15 and TBA29 to form a network of TBAs (i.e., supra-TBA15/29). The programmed hybrid-aptamers (Supra-TBA15/29) were self-assembled on GO to further boost anticoagulation activity by inhibiting thrombin activity, and thus suppress the thrombin-induced fibrin formation from fibrinogen. The Supra-TBA15/29-GO composite was formed mainly through multivalent interaction between poly(adenine) from Supra-TBA15/29 and GO. We controlled the assembly of Supra-TBA15/29 on GO by regulating the preparation temperature and the concentration ratio of Supra-TBA15/29 to GO to optimize the distance between TBA15 and TBA29 units, aptamer density, and aptamer orientation on the GO surfaces. The dose-dependent thrombin clotting time (TCT) delay caused by Supra-TBA15/29-GO was >10 times longer than that of common anticoagulant drugs including heparin, argatroban, hirudin, and warfarin. Supra-TBA15/29-GO exhibits high biocompatibility, which has been proved by in vitro cytotoxicity and hemolysis assays. In addition, the thromboelastography of whole-blood coagulation and rat-tail bleeding assays indicate the anticoagulation ability of Supra-TBA15/29-GO is superior to the most widely used anticoagulant (heparin). Our highly biocompatible Supra-TBA15/29-GO with strong multivalent interaction with thrombin [dissociation constant (Kd) = 1.9 × 10−11 M] shows great potential as an effective direct thrombin inhibitor for the treatment of hemostatic disorders.